The development of African organisational politics in South Africa, with particular emphasis on the responses of Africans to the process of unification, 1899-1910 - Odendaal, André (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1980.